Cemetery dance - Preston, Douglas J. (New York : Hachette Book, 2009)
After New York Times reporter William Smithback and his wife Nora Kelly, a Museum of Natural History archaeologist, are brutally attacked in their apartment on Manhattan's Upper West Side, Pendergast--the world's most enigmatic FBI Special Agent--returns to New York City to investigate a murderous Obeah cult.
Keywords: Pendergast, Aloysius -- (Fictitious character) -- Fiction; Obeah (Cult) -- Fiction; Murder -- Investigation -- Fiction; Government investigators -- Fiction; New York (N.Y.) -- Fiction; Psychological fiction; Suspense fiction; Occult fiction